A Combined Experimental and Theoretical DFT (B3LYP and CAMB3LYP) Study on Spectral Features (FT-IR, NMR, and UV-Visible), First-order Hyperpolarizability, NBO and HOMO-LUMO Analysis of 4-(dimethylamino)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one - Fatma, Shaheen; Rai, Sonam; Devi, Poornima; Bishnoi, Abha (Letters in Organic Chemistry, 2023)
The pyrazolone subordinate, aminopyrine, has been broken down tentatively and hypothetically for its vibrational frequencies. The chemical shift values and symphonious vibrational frequencies as obtained at B3LYP/CAM-B3LYP/6-31G after employing proper scaling techniques appear to match acceptably with the test perceptions. The hypothetical spectrograms for NMR, FT-IR and UV spectra of aminopyrine have been likewise developed and contrasted with the trial spectra. Determined hyperpolarizability (4.531 ×10-30 esu) showed that the particle might have a nonlinear optical (NLO) component with non-zero qualities. An investigation of hydrogen bonding, utilizing mathematical and topological boundaries, has additionally been conducted.
Keywords: Atom in Molecule (AIM)